Le vote ouvrier et l’élection de Donald Trump : histoire et limites du discours populiste - Tamara Boussac (Revue LISA)
This article examines the voting behavior of the white working class in the deindustrialized regions of the Northeast and Midwest in 2016. Although recent evolutions in American politics may account for the pro-Trump vote in the Rust Belt states, this article intends to demonstrate that working-class disaffection for the Democratic Party is also the result of a long historical process and the product of an old populist rhetoric that political elites have regularly used throughout the 20th century. This article questions one of the key moments in American political history, from the postwar years to the early 1970s. During this pivotal period, working-class constituencies in cities like Detroit, Chicago or Cleveland started to move away from New Deal liberalism and eventually became one of the major components of the “new Republican majority” Richard Nixon sought to form in 1972.